Role of Low-Dose EOS Imaging in the Assessment of Spinal Deformities in Children with Scoliosis - Aziz, Abdul; Ara, Iffat; Bibi, Rashada; Ahmed, Naheem; Ramachandran, Vignesh; Khan, Shaista (Journal of Neonatal Surgery, 2025)
Background: To evaluate the effectiveness of low-dose EOS imaging in assessing spinal and pelvic alignment parameters in children with scoliosis and to compare it with conventional radiography in terms of diagnostic value and radiation exposure. Methods: This cross-sectional study included 72 children with scoliosis who underwent EOS imaging between August 2023 and August 2024. Spinal parameters such as Cobb angle, sagittal vertical axis, thoracic kyphosis, lumbar lordosis, and pelvic parameters were assessed. EOS findings were compared with conventional radiographs where available. Image quality, 3D reconstruction feasibility, and radiation dose differences were also analyzed. Results: Idiopathic scoliosis accounted for 72.2% of cases, with thoracic curvature being the most common pattern. EOS provided accurate measurements of Cobb angle (mean 29.4° ± 11.6) and sagittal alignment, with significantly better visualization of thoracic kyphosis (p = 0.041). Radiation dose from EOS was nearly four times lower than standard radiographs (p < 0.001). Image quality was graded as good in 75% of cases, and 3D reconstruction was successful in over 84% of patients. Conclusion: EOS imaging offers a reliable, low-radiation, and comprehensive solution for evaluating scoliosis in children. Its ability to generate precise, full-body, and 3D spinal assessments makes it a valuable tool in pediatric orthopedic imaging